On asymptotically optimal weight quadrature formulas on classes of differentiable functions - Ligun, A. A.; Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the problem of asymptotically optimal quadrature formulas with continuous weight function on classes of differentiable functions.